Facilitating Students’ Higher Order Thinking Skill (Hots) Through Three-Phase Reading Activity at Eis Class - Muzammil, Sadulloh; Widiati, Ari; Alfarisi, Muhammad Adib (AT-TURATS, 2023)
The purpose of this research was to show how to facilitate students’ higher-order thinking skills (HOTS) in reading activities in English for Islamic Studies class and acknowledge students’ opinions on the activity. This was descriptive qualitative research, and its data were collected through observation and interview. Then the data were analyzed using interactive data analysis: data collection, data reduction, data display, and conclusion. The findings showed that the effort to facilitate students’ higher-order thinking skills (HOTS) is by proposing not only lower-level questions but also higher-level questions. To prevent the overuse of lower-level questions or higher-level questions, the lecturer employs the question-answer relationships (QAR) framework of the reading phase. The interview with students indicated that the students thought that the activity benefits them. Besides, the creative response questions in the post-reading phase enabled them to optimize their mind (schemata) proposing a solution to the problems found in the passage without feeling afraid of making mistakes as there is no wrong or right answer to such questions.